Hospitalization costs for patients colonized with carbapenemase-producing Enterobacterales during an Australian outbreak. Issue 2 (June 2020) - Rodriguez-Acevedo, A.J.; Lee, X.J.; Elliott, T.M.; Gordon, L.G.
Abstract: Background: Carbapenem-producing Enterobacterales are an expanding group of Gram-negative bacteria that are resistant to carbapenems and cause over 9000 cases of hospital-associated infections in the USA. Efforts to quantify the economic and societal burden to healthcare are important to inform resource planning to implement infection control programmes. Aim: We estimated the healthcare costs during an outbreak of carbapenemase-producing Escherichia coli OXA-181 in Australia. We aimed to understand the economic burden to hospitals of patients who are asymptomatically colonized with high-risk bacteria. Methods: Hospital admissions data and associated costs were obtained from the State Health Department. Colonized patients were matched to non-colonized patients on age, sex, admission ward and diagnostic category. Mean healthcare costs and length of stay were examined using generalized linear models and accounted for time-dependent bias, patient age and ward location. Findings: On average, colonized patients had six times higher mean costs (AU$155, 784; 95% confidence interval (CI): AU$77, 892–285, 604) than non-colonized patients (AU$25, 964). Mean costs for those aged 75–79 years were 50% lower ( P =0.02) compared with the youngest subgroup, 35–39 years of age. The mean extended length of stay was 12 days (95% CI: 3–21) for colonized patients. Nursing care was the main driver of overall costs for colonized (44%) and non-colonized (39%) patients. Conclusion: Patients colonized with carbapenem-producing Enterobacterales during an official hospital outbreak incurred higher costs than non-colonized patients. Although infected patients incur substantial economic burden to hospitals, the costs incurred by colonized patients is also high.